The banking systems of Germany, the UK and Spain form a spatial perspective: The UK case - Franz Flögel; Stefan Gärtner (Institut Arbeit und Technik (IAT), 2018)
As expected, this comparison of the German and the UK banking systems shows substantial differences between the countries. In the UK, savings banks disappeared long ago and other regional banks have never become important in lending to business. Instead, the five large commercial banks dominate business lending. Hardly any short-distance lenders still currently exist in the UK according to our qualitative distance classification of banks and other financial providers for small firms. The closure of the very last local savings bank in 2017 marks the preliminary end of traditional regional banking in the UK and indicates that the financial crisis indirectly challenges small and regional banks disproportionally. This is because the low interest rate environment and more complex banking regulations affect small and regional banks more, making it almost impossible for small standalone banks to survive. Problems in small firm finance have been discussed in the UK at least since the 1990s and government support has been given to community development financial institutions and credit unions in order to close the financial gap for small firms. Due to the financial crisis, access to finance has become increasingly difficult for small businesses, especially in remote regions, so the debate on how to reinvent local banking (and hence how to improve access to finance) has gathered momentum. Three options are under discussion. The first is to create in one stroke a regional and public banking group with a substantial market share by restructuring the Royal Bank of Scotland into a network of local and public banks. The second is to recreate regional banks on an entirely new basis with the help of a new association that would provide economies of scale and knowledge in order to enable local people to create their local banks. The third is to establish local banking by upscaling other financial providers, such as credit unions and responsible finance providers. Whether any of these options are realistic is difficult to say right now. One additional option that could improve SME finance are the so-called challenger banks, a type of bank unknown in Germany. These banks differ in terms of ownership, business model and regional market orientation, yet our findings suggest that they tend to operate on a more decentralised (short-distance) business model than large commercial banks.
Keywords: D43; E21; G01; G21; G38; R12; 330; comparing banking systems; SME finance in the UK; decentralised vs. centralised banking